Kaitlin Quick: capstone - Quick, Kaitlin, artist and filmmaker (Colorado State University. Libraries, 2018)
The artist's statement: There is more to the world than meets the eye. Our perception of our surroundings is entirely in our head. I prefer to focus on the creations of our mind rather than interpretations of the real world. I work in the surreal and fantastic, taking what we know and twisting it into something new through either dramatic manipulation or forced perspective. My art molds alternate realities that require searching for meaning beyond the surface and demand understanding beyond face value. I work with video and virtual reality to explore the possibilities in using time, immersion, and interactivity as primary aspects of art.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
Video has no spoken word.
Keywords: electronic art